2015
DOI: 10.3892/ol.2015.2952
|View full text |Cite
|
Sign up to set email alerts
|

Directional migration of adult hematopoeitic progenitors to C6 glioma in vitro

Abstract: Abstract. Multiform glioblastoma is the most common primary, highly invasive, malignant tumor of the central nervous system, with an extremely poor prognosis. The median survival of patients following surgical resection, radiation therapy and chemotherapy does not exceed 12-15 months and thus, novel approaches for the treatment of the disease are required. The phenomenon of the directed migration of stem cells in tumor tissue presents a novel approach for the development of technologies that facilitate the tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Mammalian and human postnatal stem cells possess pronounced anti-tumor potential, while they are capable of directed migration to and interaction with tumor cells. Previous studies by our group ( 83 , 84 ) and studies by other researchers ( 85 , 86 ) have described this phenomenon using models of gliomas, metastatic melanoma ( 87 ), solid tumors ( 88 ) and CSCs of metastatic tumors ( 89 ). The vector of migration activity for normal tissue-specific stem cells in relation to GBM cells is inversely proportional to the differentiation level of cancer cells and is more pronounced among cells with one histogenetic source in the brain ( 86 ) that allows to target CSCs directly using neural stem cells.…”
Section: Biomedical Cellular Technologies In Glioblastoma Therapymentioning
confidence: 78%
See 1 more Smart Citation
“…Mammalian and human postnatal stem cells possess pronounced anti-tumor potential, while they are capable of directed migration to and interaction with tumor cells. Previous studies by our group ( 83 , 84 ) and studies by other researchers ( 85 , 86 ) have described this phenomenon using models of gliomas, metastatic melanoma ( 87 ), solid tumors ( 88 ) and CSCs of metastatic tumors ( 89 ). The vector of migration activity for normal tissue-specific stem cells in relation to GBM cells is inversely proportional to the differentiation level of cancer cells and is more pronounced among cells with one histogenetic source in the brain ( 86 ) that allows to target CSCs directly using neural stem cells.…”
Section: Biomedical Cellular Technologies In Glioblastoma Therapymentioning
confidence: 78%
“…3A–D . This phenomenon is observed in 40% of C6 glioma cells, 77% of lung cancer cells (А549), 47% of breast adenocarcinoma cells and 64% of human glioblastoma cells ( 83 , 84 ).…”
Section: Biomedical Cellular Technologies In Glioblastoma Therapymentioning
confidence: 93%
“…Bryukhovetskiy et al reported that cancer stem cells (CSCs) were very difficult to destroy and could recruit other types of stem cells, and they proteomically identified an interaction between CSCs and hematopoietic stem cells (HSCs). 115,116 An animal model has confirmed this hypothesis, 117 and a clinical trial (NCT01759810) investigating concurrent HSCs, DC vaccines and cytotoxic lymphocytes in the treatment of GBM has been conducted. 58 In addition to cellbased vaccines, other cell-based immunotherapies, such as adoptive cellular therapy (ACT), have shown potential feasibility for clinical application.…”
Section: Tumor Cell Vaccinesmentioning
confidence: 91%
“…However, experimental data show that the original source of cytokines can be tumor cells themselves (51,52). Having autonomy, they can synthesize their own cytokines.…”
Section: Theoretical Prerequisites For Using Cell and Post-genome Tecmentioning
confidence: 99%